Elevated growth [CO2] enhances heat stress resistance of photosynthesis in young leaves of avocado (Persea americana) - Abiola, Yusuph Olawale; Sulaiman, Hassan Yusuf; Kaurilind, Eve; Niinemets, Ülo (Frontiers in Plant Physiology, 2025)
Climate change is associated with higher atmospheric [CO2] and more frequent temperature extremes, with the strongest impact expected in the tropics where plants often operate close to their heat stress limit. How the resistance of foliage photosynthetic traits to heat stress varies with [CO2] elevation remains largely unknown, particularly in tropical species with continuously expanding canopies, where the heat resistance of leaves can vary with age. We studied the impact of heat shock stress resembling heatflecks due to fluctuating light (48 °C for 10 min) on foliage physiological traits and chemical contents in young-mature and old-mature foliage of the tropical species Persea americana Mill. plants grown under ambient (400 μmol mol-1) and elevated (800 μmol mol-1) [CO2]. Leaf characteristics were studied through a 48 h recovery period. Light-saturated net assimilation rate (A) decreased with leaf age in both ambient and elevated [CO2]. In young-mature leaves, A in plants grown under elevated [CO2] was greater than A in plants grown under ambient [CO2]. In old-mature leaves, A was similar under both [CO2] and this was associated with increased nutrient limitation under elevated [CO2]. Upon heat stress application, A decreased in all cases due to both reduction in stomatal conductance and inhibition of biochemical photosynthetic capacity (maximum Rubisco carboxylase activity). During recovery, A increased to pre-stress level in all but in young-mature plants grown under ambient [CO2] where A remained much lower (78% reduction) than in control plants. As young leaves have a longer remaining lifespan and higher future potential contribution to plant carbon gain, preservation of photosynthetic capacity in young leaves under elevated [CO2] suggests that elevated [CO2] can enhance long-term photosynthetic production in P. americana exposed to heat episodes.